The influence of combinations of oximes on the reactivating and therapeutic efficacy of antidotal treatment of soman poisoning in rats and mice - Kassa, Jiří; Žďárová Karasová, Jana; Caisberger, Filip; Bajgar, Jiří (Toxicology mechanisms and methods, 2009)
The influence of the combination of oximes on the reactivating and therapeutic efficacy of antidotal treatment of acute soman poisoning was evaluated. The ability of two combinations of oximes (HI-6 + trimedoxime and HI-6 + K203) to reactivate soman-inhibited acetylcholinesterase and reduce acute toxicity of soman was compared with the reactivating and therapeutic efficacy of antidotal treatment involving single oxime (HI-6, trimedoxime, K203) using in vivo model. Studies determining percent of reactivation of soman-inhibited blood and diaphragm acetylcholinesterase in poisoned rats showed that the reactivating efficacy of both combinations of oximes is slightly greater than the reactivating efficacy of the most effective individual oxime, but the difference among them is not significant. Both combinations of oximes were found to be as effective in the reduction of acute lethal toxic effects in soman-poisoned mice as the antidotal treatment involving the most efficacious individual oxime. Thus, the efficacy of oximes is comparative in rats vs mice. A comparison of reactivating and therapeutic efficacy of individual oximes showed that the newly developed oxime K203 is approximately as effective as commonly used trimedoxime; nevertheless, their reactivating and therapeutic efficacy is markedly lower compared to the oxime HI-6. Based on the obtained data, one can conclude that the antidotal treatment involving chosen combinations of oximes does not significantly influence the potency of the most effective individual oxime (HI-6) to reactivate soman-inhibited rat acetylcholinesterase and to reduce acute toxicity of soman.
Keywords: soman; zvířata; trimedoxim; fixní kombinace léků; Cholinesterase Reactivators; Oximes; Chemical Warfare Agents; oximy; Animals; Drug Combinations; potkani Wistar; cholinesterasové inhibitory; antidota; Trimedoxime; Soman; Antidotes; Mice; Pyridinium Compounds; Rats; Male; pyridinové sloučeniny; mužské pohlaví; myši; krysa rodu Rattus; Rats, Wistar; chemické bojové látky; reaktivátory cholinesterasy; Cholinesterase Inhibitors